Social, emotional and behavioural difficulties associated with persistent speech disorder in children: A prospective population study - Wren, Yvonne; Pagnamenta, Emma; Orchard, Faith; Peters, Tim J.; Emond, Alan; Northstone, Kate; Miller, Laura Louise; Roulstone, Susan (JCPP advances, 2023)
Purpose Social, emotional and behavioural difficulties (SEBD) in childhood are associated with negative consequences across the life course. Children with developmental language disorder have been identified as being at risk of developing SEBD but it is unclear whether a similar risk exists for children with speech sound disorder, a condition which impacts on children's ability to make themselves understood and has been shown to be associated with poor educational outcomes. Methods Participants were children who attended the 8‐year‐old clinic in the Avon Longitudinal Study of Parents and Children (N = 7390). Children with speech sound disorder that had persisted beyond the period of typical speech acquisition (persistent speech disorder [PSD]) at age 8 were identified from recordings and transcriptions of speech samples (N = 263). Parent‐, teacher‐ and child‐reported questionnaires and interviews including the Strengths and Difficulties Questionnaire, Short Moods and Feelings Questionnaire and measures for antisocial and risk‐taking behaviour were used to provide outcome scores for SEBD at 10–14 years in a series of regression analyses. Results Following adjustment for biological sex, socio‐economic status and Intelligence Quotient, children with PSD at age 8 were more likely to show peer problems at age 10–11 years compared with their peers, as reported by teachers and parents. Teachers were more likely to report problems with emotionality. Children with PSD were no more likely to report symptoms of depression than their peers. No associations were observed between PSD, risk of antisocial behaviour, trying alcohol at age 10 or smoking cigarettes at age 14. Conclusions Children with PSD may be at risk in terms of their peer relationships. This could impact on their wellbeing and, while not observed at this age, may lead to depressive symptoms in older childhood and adolescence. There is also the potential that these symptoms may impact on educational outcomes.